Simultaneous comprehensive multiplex autoantibody analysis for rapidly progressive glomerulonephritis. Issue 44 (November 2016) - Sowa, Mandy; Trezzi, Barbara; Hiemann, Rico; Schierack, Peter; Grossmann, Kai; Scholz, Juliane; Somma, Valentina; Sinico, Renato Alberto; Roggenbuck, Dirk; Radice, Antonella
Abstract : Abstract: Rapidly progressive glomerulonephritis (RPGN) is mainly caused by anti-glomerular basement membrane (GBM) antibody-mediated glomerulonephritis, immune-complex or anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitides and leads to rapid loss of renal function. Detection of ANCA and autoantibodies (autoAbs) to GBM and dsDNA enables early diagnosis and appropriate treatment of RPGN aiding in preventing end-stage renal disease. Determination of ANCA on neutrophils (ANCA) as well as autoAbs to myeloperoxidase (MPO-ANCA), proteinase 3 (PR3-ANCA), GBM, and dsDNA was performed by the novel multiplex CytoBead technology combining cell- and microbead-based autoAb analyses by automated indirect immunofluorescence (IIF). Forty patients with granulomatosis with polyangiitis (GPA), 48 with microscopic polyangiitis (MPA), 2 with eosinophilic GPA, 42 with systemic lupus erythematosus (SLE), 43 with Goodpasture syndrome (GPS), 57 with infectious diseases (INF), and 55 healthy subjects (HS) were analyzed and findings compared with classical single testing. The CytoBead assay revealed for GPA, MPA, GPS, and SLE the following diagnostic sensitivities and for HS and INF the corresponding specificities: PR3-ANCA, 85.0% and 100.0%; MPO-ANCA, 77.1% and 99.1%; anti-GBM autoAb, 88.4% and 96.4%; anti-dsDNA autoAb, 83.3% and 97.3%; ANCA, 91.1% and 99.1%, respectively. Agreement with classical enzyme-linked immunosorbent assay and IIF was very good for anti-GBM autoAb, MPO-ANCA, PR3-ANCA, and ANCA, respectively. Anti-dsDNA autoAb comparative analysis demonstrated fair agreement only and a significant difference ( P = 0.0001). The CytoBead technology provides a unique multiplex reaction environment for simultaneous RPGN-specific autoAb testing. CytoBead RPGN assay is a promising alternative to time-consuming single parameter analysis and, thus, is well suited for emergency situations.